The status of relationship between coping strategies and quality of life in women with polycystic ovary syndrome - Morshedi, Tahereh (J Educ Health Promot, 2021)
BACKGROUND: Polycystic ovary syndrome (PCOS) has a profound effect on patients’ quality of lives; and it is important to identify the affecting factors. The aim of this study was to assess the status of and relationship between coping strategies and quality of life in women with PCOS. MATERIALS AND METHODS: In this cross-sectional study, we recruited 200 married women (20–50 years old) with PCOS from Arash and Bu Ali hospitals in Tehran in 2019–2020. Data were collected using the two following questionnaires: Coping strategies and quality of life. Data were analyzed using the regression analysis test in the SPSS-21. RESULTS: The results showed that 119 (59.5%) participants were identified with increased hirsutism, 166 (83%) women were obese, 140 (70%) had irregular menstruation and 136 participants (68%) had painful menstruation as the side effects of PCOS. Sixty nine (34.5%) individuals reported unknown side effects. There was a relationship between emotional coping strategy and problem solving coping strategy with quality of life (beta = 0.270 and 0.219, respectively). CONCLUSION: Patients with PCOS were more likely to use emotional coping strategies. Low quality of life exacerbated symptoms of the disease.